IMPLEMENTASI METODE PERSONAL EXTREME PROGRAMMING DALAM PERACANGAN APLIKASI PEMESANAN RUANG RAPAT BERBASIS ANDROID DISKOMINFO JAWA TIMUR - Akbar, Muhammad Sulthoni; Nuryasin, Ilyas; Chandranegara, Didih Rizki (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
The advancement of information technology greatly enhances human activities, including the introduction of information management and meeting room reservation systems. In the East Java Provincial Office of Communication and Informatics, manual room reservation processes pose challenges, especially when administrators are unavailable. To address this, a research project aims to develop an IT-based application for efficient meeting room management and reservation. This will simplify the process for employees, enabling systematic and effective room bookings. The application allows users to check room availability online in real-time, eliminating the need for direct interaction with administrators. This implementation is expected to significantly enhance the overall efficiency of the East Java Provincial Office of Communication and Informatics. The application development will follow Personal Extreme Programming (PXP), known for its adaptability in software development. PXP involves stages like requirements, planning, design, implementation, and testing, iterated as needed. Successful application of PXP relies on skilled developers, requiring clear requirement identification and accurate work estimation. This research builds upon prior studies demonstrating accelerated project completion using PXP. It aims to provide insights into applying PXP for flexible software development, emphasizing information technology's role in enhancing organizational efficiency.